Means of Corporate Crisis Management - Bivainis, Juozas; Garškaitė, Kristina (Ekonomika, 2002)
Corporate crisis management became one of the most popular terms in business practice. However, its content is not strictly defined.Foreign economists describe crisis management as activities intended to overcome such situation of a corporate when the corporate faces the threat on its existence and a survival of the corporate is the main goal. Application of intensive strict and rapid means and methods intended to overcome the existing crisis situation in a corporate is characteristic for such activities. Other authors underline a becoming free and positive aspect of crisis. They describe crisis management as a formation of certain instruments, which would inform about the oncoming turning point, and would allow choosing of. new direction of development.While summarizing the mentioned descriptions of crisis management il is possible to stale that corporale crisis management is a preparation and implementation of a set of means allowing normalizing of business-financial activities of a corporate facing with threat of bankruptcy.Choice of a set of means of crisis management depends on many factors and conditions that determine the order of priority of means, priorities in each certain case. Purpose of crisis management first of all is a rapid restoration of corporate solvency within a short period, and secondly, a restoration of corporate financial stability and assurance of financial balance within a long period.Means of corporate crisis management are various, based on different principles. Due to broad their diapason there is no a simple necessity to apply them. A set of means joining most important provisions of crisis management should be formed for effective corporate crisis management. Its success also depends on a correct evaluation of situation in a corporale and a choice of adequate means.Corporate crisis management differs from ordinary management. All means and methods of ordinary management are intended to support and develop corporate activities (including steps allowing to avoid crisis situation) in present and oncoming period. Means of corporate crisis management are intended for overcoming of a crisis, which has already existed.